Role of the Autonomic Nervous System in Atrial Fibrillation: Pathophysiology and Therapy - Chen, Peng-Sheng (2014)
Autonomic nervous system activation can induce significant and heterogeneous changes of atrial electrophysiology and induce atrial tachyarrhythmias, including atrial tachycardia (AT) and atrial fibrillation (AF). The importance of the autonomic nervous system in atrial arrhythmogenesis is also supported by circadian variation in the incidence of symptomatic AF in humans. Methods that reduce autonomic innervation or outflow have been shown to reduce the incidence of spontaneous or induced atrial arrhythmias, suggesting that neuromodulation may be helpful in controlling AF. In this review we focus on the relationship between the autonomic nervous system and the pathophysiology of AF, and the potential benefit and limitations of neuromodulation in the management of this arrhythmia. We conclude that autonomic nerve activity plays an important role in the initiation and maintenance of AF, and modulating autonomic nerve function may contribute to AF control. Potential therapeutic applications include ganglionated plexus ablation, renal sympathetic denervation, cervical vagal nerve stimulation, baroreflex stimulation, cutaneous stimulation, novel drug approaches and biological therapies. While the role of the autonomic nervous system has long been recognized, new science and new technologies promise exciting prospects for the future.